ENHANCING BUSINESS WRITING SKILLS THROUGH INTERCULTURAL COMMUNICATIVE COMPETENCE: AS A STRATEGY TO TEACH NON-ENGLISH DEPARTMENT STUDENTS - Soraya, Irma; Kusumajanti, Wahju; Rusnalasari, Zulidyana Dwi; Avifah, I’anatul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Intercultural Communicative Competence (ICC) is the ability to communicate and interact effectively and appropriately in various cultural contexts. ICC could serve as a strategic approach to address cultural norms and differences within a business context. In terms of enhancing the cultural awareness of non-English department students, ICC stimulated students to confront the realities of the global marketplace with various norms of communication. This study investigates the impact of Intercultural Communicative Competence (ICC) on the business writing skills as a strategy to teach non-English department students at UIN Sunan Ampel Surabaya. The primary objective is to determine how ICC as a teaching strategy can enhance students' ability to produce effective business documents in a globalized context. Utilizing a mixed-methods approach, the research incorporates both quantitative surveys and qualitative interviews to gather comprehensive data from participants. Key findings reveal that ICC approach exhibits significantly improved business writing skills of students. The study underscores the importance of integrating ICC training into business education curricula as a strategy to prepare students for the demands of international business environments. These findings suggest that fostering intercultural awareness and competence is crucial for developing proficient business communicators, thereby enhancing overall business education and facilitating effective intercultural communication in professional settings. Keywords: Business writing skills; Intercultural Communicative Competence; English Teaching Strategy.